2014
DOI: 10.1107/s1600576714001939
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic effect of a high magnetic field on a solidified hypoeutectic Zn–Al alloy

Abstract: Hypoeutectic Zn-4.45 wt% Al solidified under a high magnetic field was investigated crystallographically. With the field, the primary zinc-rich phase is distributed homogeneously and orients with the c axis perpendicular to the magnetic field direction. These results are attributed to the magnetic viscosity resistance force and the magnetocrystalline anisotropy of zinc, respectively. The orientation modification also leads to a preferential alignment of the flat-shaped primary dendrites. Furthermore, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Therefore, it is of fundamental interest to study its growth under HMFs. In other work, it has been shown that the primary zinc-rich crystals in Zn-Al [13] and Zn-Sn [14,26] alloys have a dendritic form (preferentially grow along < 101 0 > and/or <0001>) and can be preferentially aligned and oriented by HMFs. According to some recent work, the primary zinc-rich crystals in ternary Sn-Zn-Bi solder alloys usually exhibit a needle-like morphology in two dimensions [27].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, it is of fundamental interest to study its growth under HMFs. In other work, it has been shown that the primary zinc-rich crystals in Zn-Al [13] and Zn-Sn [14,26] alloys have a dendritic form (preferentially grow along < 101 0 > and/or <0001>) and can be preferentially aligned and oriented by HMFs. According to some recent work, the primary zinc-rich crystals in ternary Sn-Zn-Bi solder alloys usually exhibit a needle-like morphology in two dimensions [27].…”
Section: Resultsmentioning
confidence: 96%
“…Crystals 2017, 7, 204 2 of 10 (usually negligible in conventional magnetic fields), thereby imposing more abundant effects on the structures of the alloys [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It has been found that the HMFs could orient and align the structures [13][14][15][16][17], increase the phase transformation temperature [19], enhance the magnetic coercivities [16], suppress the diffusion of solute elements [21], modify the orientation relationship between the eutectics [22], and change the solid-liquid interface morphologies [23]. Hexagonal close-packed zinc is characterized by large solid-liquid interfacial energy anisotropy [24,25] and magnetocrystalline anisotropy [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coating formation on metal and alloy surfaces is one of the most common ways to protect items from environmental impacts [1][2][3][4] and to specifically func tionalize their surfaces [5][6][7]. Plasma electrolytic oxi dation (PEO) is an outstanding route to form protec tive coatings [see 8-10 and other references].…”
mentioning
confidence: 99%